ANALISIS KINERJA GURU BERDASARKAN DAMPAK KEMAMPUAN MANAJERIAL KEPALA SEKOLAH, MOTIVASI KERJA DAN IKLIM ORGANISASI (Studi Kasus di SMA Negeri se-Kecamatan Peusangan Kabupaten Bireuen) - Jasmiati Jasmiati; Kamaruddin Kamaruddin (IndOmera, 2026)
The study of employee and teacher performance is an interesting one. This study examines the impact of factors such as the managerial ability of the principal, teacher motivation, and the school's organizational climate, which are thought to fully support teacher performance. A quantitative associative research method was used, utilizing path analysis as a statistical tool. The research subjects were all 102 teachers at public high schools in Peusangan District, Bireuen Regency. The results revealed: (1) Teacher performance is influenced by the principal's managerial ability, both directly and indirectly through teacher motivation and the school's organizational climate, by 59.01%. (2) Work motivation influences teacher performance, both directly and indirectly through the principal's managerial ability and organizational climate, by 40.52%. (3) Teacher performance is influenced by the organizational climate, both directly and indirectly through the principal's managerial ability and teacher motivation, by 53.71%. (4) All three simultaneously contribute significantly to teacher performance by 61.4%. (5) There is a causal relationship between the variables of managerial ability, work motivation, and organizational climate, with a moderate categorization.